Rockslides and rock avalanches in the Central Andes of Argentina and their possible association with permafrost degradation. (30th August 2019) - Tapia Baldis, Carla; Trombotto Liaudat, Dario
Abstract: The identification of hazardous slopes with degrading permafrost is a key task in the mountain periglacial environment. If rockslides have previously been preconditioned by rock wall permafrost, similar events may be triggered from present unstable rock walls. An inventory of rockslides and rock avalanches in the austral part of the Santa Cruz river basin (31°40′–31°50′S, 70°30′–70°10'W), San Juan, Argentina, was made. The study area comprises a surface of approximately 432 km 2 (50% above 3, 500 m asl); 15 rockslides, 12 complex rockslides evolving to rock avalanches and 19 rock avalanches were identified. The deposits were analyzed with remote sensory imagery and during fieldwork in order to study processes under permafrost degradation caused by global warming. Rock sampling procedures and laboratory rock‐resistivity testing were also carried out. We characterized the detachment scars and deposits for two rockslides. Two different mechanisms were identified. In one rockslide, shallow active layer detachment was favored by shear‐displacement along pre‐existing joints, as a result of short‐term periods of climate warming. In the other, long‐term permafrost degradation favored a deeper failure process. The studied landslide processes could not be explained by permafrost degradation alone. Faults, the geometric arrangement of their structural elements and seismic activity may contribute to trigger these phenomena. It is expected that the magnitude and frequency of rockslide hazards will increase during the 21st century.